A steroidal lactone, withaferin A acts as a potential insect growth regulator against polyphagous pest, Spodoptera litura (Lepidoptera: Noctuidae). (21st July 2021) - Gaur, Sandeep Kumar; Kumar, Krishna
Abstract: Administration of a steroidal lactone, withaferin A to last larval instar of a polyphagous pest, Spodoptera litura caused severe impairment of development resulting into a significant delay in larval–pupal and pupal–adult ecdysis, larval mortality, ecdysial stasis, formation of larval–pupal and pupal–adult intermediates, suppression of pupation and adult emergence and formation of abnormal pupae and adultoids. The LC50 value in topical administration of withaferin A was 180.3 µg·µL −1 against freshly moulted sixth instar larvae of S. litura . This suggests that a bioactive ingredient withaferin A, found in the parts of the medicinal plant, Withania somnifera interferes with the neuroendocrine system of the insects resulting into disruption of moulting and metamorphosis. The active ingredient, withaferin A from W. somnifera may be safely and judiciously employed for the control of S. litura under field conditions along with other bio-rational approaches for insect pest management programs.